Peran Mediasi Kepuasan Kerja terhadap Hubungan Antara Workload dan Work Place Relationship terhadap Kinerja Kerja Guru SMA Katolik Frateran Ndao - Simon Petrus Sony Wany; Rafael Octavianus Byre (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research (1). To analyze the influence of workload on work performance (2). To analyze the influence of workplace relations on work performance (3). To analyze whether job satisfaction has an effect on work performance (4). To analyze whether workload has an effect on job satisfaction (5). To analyze whether Workplace Relations has an effect on job satisfaction (6). To analyze whether Workload has an effect on work performance mediated by job satisfaction (7). To analyze whether Workplace Relations has an effect on work performance mediated by job satisfaction. This research uses a quantitative approach with a survey research design. The data used uses survey research. Data was collected through questionnaires distributed to teachers at Frateran Ndao Catholic High School. Data analysis was carried out using descriptive and inferential statistical methods, including path analysis to examine the mediating role of Job Satisfaction on the Relationship between Workload and Workplace Relationship on Catholic High School Teacher Work Performance. Ndao Brotherhood. The results of this research The first hypothesis tests the effect of Workload on work performance. The test results show that the T statistic for Workload on work performance is 2.541. From the test results it is stated that the t-statistic is significant because the value is greater than 1.96 (t table) with a p value of 0.011 <0.05 so that the first hypothesis in this study can be accepted. The second hypothesis tests the influence of Workplace Relationships on work performance. The test results show that the T statistic of Workplace Relationship on work performance is 2.353. From the test results it is stated that the t-statistic is significant because the value is greater than 1.96 (t table) with a p value of 0.019 <0.05 so that the second hypothesis in this study can be accepted.